Attenuated vagally-mediated heart rate variability at rest and in response to postural maneuvers in patients with generalized anxiety disorder. Issue 9 (7th July 2020) - Chang, Hsin-An; Fang, Wen-Hui; Wan, Fang-Jung; Tzeng, Nian-Sheng; Liu, Yia-Ping; Shyu, Jia-Fwu; Chang, Tieh-Ching; Huang, San-Yuan; Chang, Chuan-Chia
Abstract: Background: Altered heart rate variability (HRV), an index of autonomic nervous system function, has been reported in generalized anxiety disorder (GAD), but the results have been mixed. Thus, the present study, using a large sample size and better methodology, aims to examine whether GAD is associated with impaired HRV, both at rest and in response to posture challenges. Methods: In total, 1832 participants were recruited in this study, consisting of 682 patients with GAD (including 326 drug- and comorbidity-free GAD patients) and 1150 healthy controls. Short-term HRV was measured during the supine-standing-supine test (5-min per position). Propensity score matching (PSM), a relatively novel method, was used to control for potential confounders. Results: After PSM algorithm, drug- and comorbidity-free GAD patients had reductions in resting (baseline) high-frequency power (HF), an index for parasympathetic modulation, and increases in the low-frequency/HF ratio (LF/HF), an index for sympathovagal balance as compared to matched controls. Furthermore, the responses of HF and LF/HF to posture changes were all attenuated when compared with matched controls. Effect sizes, given by Cohen's d, for resting HF and HF reactivity were 0.42 and 0.36–0.42, respectively. Conclusions: GAD is associated with altered sympathovagal balance, characterized by attenuation in both resting vagal modulation and vagal reactivity, with an almost medium effect size (Cohen's d ≈ 0.4), regardless of medication use or comorbidity status.